IS MAKING A SHOPPING LIST AN EFFECTIVE WAY OF PREVENTING CONSUMERS FROM MAKING IMPULSE PURCHASE? - RAJA SHARAH FATRICIA (Jurnal Manajemen Terapan dan Keuangan, 2016)
In this research an experimental study has to be designed. The goal is to develop an experimental procedure that will answer the research question of choice. Subjects for research questions were given to choose from. The research question we have chosen is: “Is making a shopping list an effective way of preventing consumers from making impulse purchases?” This research question is chosen because it seems quite logical that people with a shopping list will only buy the products on that list. They most probably will look only on the list and look for the products in the store rather than looking around in the store and pick products they see and think they’re also nice to have. To make things a bit more interesting, we have modified this research question and added an extra variable is added, being “time”. It might be interesting to see whether people who have a shorter time to shop will only buy the most necessary products. People with less time cannot walk around in the store calmly and evaluate many products for necessity. Our research question is as follows: “Are the use of a shopping list and available time for shopping predictors for impulse buying?”